A Case Study on Comparison of High School Students’ Scientific Literacy Competencies Domain in Physics with Different Methods: Pbl-Stem Education, Pbl, and Conventional Learning (Jurnal Pendidikan IPA Indonesia, 2020)
Literacy skill is needed in the 21st century learning, whereas research about the implementation of Problem Based Learning-Science Technology Engineering and Mathematics (PBL-STEM) to develop students’ ability of scientific literacy is still limited. This research purposed to compare students’ scientific literacy competencies domain improvement through PBL-STEM in the topic of optical instrument. The quasi-experiment non-equivalent group design involved the students of Senior High School 9 Malang Indonesia in three classes called PBL-STEM, PBL, and control class. PBL-STEM class made three products, which were camera obscura, magnifier, and binoculars, which were presented with posters and reports. The PBL class, on the other hand, only made binoculars and presented their work briefly. Scientific Literacy Ability Test was used with 0.88 Cronbach’s alpha reliability. Data analysis with one-way ANOVA, post hoc Tukey test, N-gain, and Cohen’s effect size was conducted. The result showed that three classes had a significantly different ability in scientific literacy. Scientific literacy competencies domain of PBL-STEM was the highest, while PBL class is higher than the control class. The improvement of both PBL-STEM and PBL belonged in medium category, whereas the improvement in the control class was in low category. The effect of the operational implementation of PBL-STEM and PBL pair yielded large result, and both PBL-STEM and control and PBL and control pairs yielded very large category in the improvement of students’ scientific literacy.